Sensuous unity of art and science : the times of Rudolf II - Valsiner, Jaan (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"The goal of this book is to locate the birth pangs of psychology-the study of the psyche- in the Renaissance unity of art and science. The historical period 1583-1611 in Prague was a particularly productive for all Europe in its intellectual advancements in art and science. It was facilitated by the special personality of the Holy Roman Emperor Rudolf II who during his reign made Prague the capital of the Empire where the major artists, scientists, architects and alchemists came together in the service of the Emperor and formed a unique context of interdisciplinary synthesis of ideas that enhanced European philosophies, sciences, and arts in the following centuries. While the history of art in and astronomy in the Rudolfine era has been amply covered, the impacts of the intellectual atmosphere of the era on psychology, philosophy, social ideologies, and aesthetics has remained scarcely investigated. The volume includes analyses of history of ideas in psychology, sociology and other social sciences that received the impetus of the political situation of Rudolfine Prague with religious tolerance and decline of the political power of the Holy Roman Empire"-- Provided by publisher.
Keywords: Rudolf -- II, -- Holy Roman Emperor, -- 1552-1612.; Science -- Czech Republic -- Prague -- History -- 16th century.; Arts -- Czech Republic -- Prague -- History -- 16th century.; Psychology -- History -- 16th century.; Prague (Czech Republic) -- Intellectual life.; Holy Roman Empire -- Intellectual life.; Psychology -- History.; Psychology.; History: specific events and topics.; elektronické knihy; electronic books